CAMELLIA PYRIFORMIS (THEACEAE, SECTION CALPANDRIA), A NEW SPECIES FROM NORTHERN VIETNAM - Ngoc Bon Trinh; Van Quang Le; Thanh Son Hoang (Tạp chí Khoa học Đại học Đà Lạt)
Camellia pyriformis is described, illustrated, and placed in section Calpandria. Morphological features of this new species are young branches villous; leaves above pubescent, a long midrib, below pubescent; petiole falcate, densely villous; flowers solitary or geminate; pedicel very short, pubescent; bracteoles sparsely pubescent on both sides; sepals, pubescent on both sides; petals, white, glabrous; androecium 5–6 stamens, filaments completely united to form a truncated cone, glabrous, basal adnate to the petal, shallowly dentate at the apex, each filament bearing an anther; gynoecium 3-locular, densely white silky strigose tomentose, styles glabrous; capsule pyriform, pubescent; seed broad pyriform, densely villous